2011
DOI: 10.1021/ef101375g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Trench Configuration on Deposition From Fine Coal Flyash near Film Cooling Holes

Abstract: Particulate deposition experiments were performed in a turbine accelerated deposition facility to examine the effects of flyash particle size and trench configuration on deposits near film cooling holes. Deposition on two bare metal Inconel coupons was studied, with hole spacings (s/d) of 3.4 and 4.5. Two sizes of sub-bituminous coal ash particles were used, with mass mean diameter of 4 and 13 μm, respectively. The effect of a cooling trench at the exit of the cooling holes was also examined in this deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…affect the evolution of deposits. As discussed earlier, the TADF, developed at BYU, has been employed to perform numerous studies of the factors affecting deposition ([6], [10], [14], [15], [16], [17], [18], and [19]). Bons et al [6] performed a study examining the deposition from four different materials: straw, sawdust, coal and petroleum coke (petcoke).…”
Section: Relevant Variables In Depositionmentioning
confidence: 99%
“…affect the evolution of deposits. As discussed earlier, the TADF, developed at BYU, has been employed to perform numerous studies of the factors affecting deposition ([6], [10], [14], [15], [16], [17], [18], and [19]). Bons et al [6] performed a study examining the deposition from four different materials: straw, sawdust, coal and petroleum coke (petcoke).…”
Section: Relevant Variables In Depositionmentioning
confidence: 99%
“…The method developed by Jensen et al [7] was later used by Ai et al [13] who used the TADF to observe deposition and its effects on trenched film-cooling holes at various impingement angles. Without deposition, the trench improved cooling at shallow impingement angles; however, during deposition simulation, particles accumulated inside the downstream lip of the trench leading to hole blockage and reduced cooling.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…It was found that the deposition rate increased with increasing gas temperature and particle size. Ai et al [12] explored the effects of particle size on deposition by using a flat plate with film-cooling holes angled at 45 • . Bonilla et al [13] further explored the particle size effect on the CFM56-5B nozzle guide vane.…”
Section: Introductionmentioning
confidence: 99%